Clinic evaluation of cognitive impairment in post-COVID syndrome: Performance on legacy pen-and-paper and new digital cognitive tests - Aysha Mohamed Rafik Patel; Gina Gilpin; Anna Koniotes; Catherine Warren; Cian Xu; Paul W. Burgess; Dennis Chan (Brain, Behavior, & Immunity - Health)
Background: Cognitive impairment, colloquially termed “brain fog”, is one of the most prevalent manifestations of post-Covid syndrome and a major contributor to impaired daily function and reduced quality of life. However, despite the high numbers of affected individuals presenting to clinical services with cognitive impairment, little work has been undertaken to date on the suitability of current memory clinic tests for identifying the cognitive deficits in this new acquired cognitive disorder.The aim of this study was therefore to determine the performance of people with post-Covid syndrome presenting with cognitive impairment on the Addenbrooke's Cognitive Examination-III (ACE-III), a cognitive test used widely in memory clinics. A subset of individuals also underwent testing on a novel battery of short digital tests assessing attention, speed of information processing and executive function, representing the domains primarily implicated in post-Covid cognitive dysfunction. Methods: 102 individuals with post-Covid syndrome presenting with subjective cognitive complaints were recruited from a specialist cognitive long Covid clinic at University Hospitals Sussex NHS Trust. All participants completed self-report questionnaires on depression, anxiety, sleep and fatigue. Cognitive performance was assessed using the ACE-III, with 20 participants also being tested on the digital Long COVID Assessment Battery (LCCAB) (N = 20). Results: The overall sample had a mean ACE-III score of 91/100 (SD 6) with 15.7% (16/102) scoring at or below the cut-off score considered to represent objective cognitive impairment. Of the 20 individuals who also completed the LCCAB, 89.47% were impaired on at least one task, primarily in the domains of attention, executive function and processing speed. Cognitive performance was not associated with depression, anxiety, sleep quality or fatigue. Conclusion: The vast majority of individuals with post-Covid syndrome presenting with subjective cognitive complaints do not exhibit impaired performance on the ACE-III. This likely reflects the historical use of ACE-III and other pen and paper cognitive tests to detect cognitive impairment in diseases causing dementia, but they are ill-equipped to identify impairment in those cognitive domains affected in post-Covid syndrome. The LCCAB detected cognitive impairments in nearly 90% of participants, primarily affecting attention, executive function, and processing speed. These observations highlight the need for alternative cognitive tests for use in routine clinical practice to detect the impairments in new acquired cognitive disorders that are not adequately captured by legacy tests.